Intravenous immunoglobulin for mortality and inflammatory status in patients with sepsis: a retrospective database study - Takano, Hayabusa; Kanda, Naoki; Wakimoto, Yuji; Ohbe, Hiroyuki; Nakamura, Kensuke (Frontiers in Immunology, 2025)
BackgroundSepsis is a life-threatening condition caused by severe infection. The efficacy of intravenous immunoglobulin (IVIG) as adjunctive therapy on mortality remains controversial. Moreover, IVIG may favorably affect sepsis-induced immunosuppression like persistent inflammation, immunosuppression, and catabolism syndrome (PICS).MethodsThis study was a retrospective cohort study using inpatient claims database provided by Medical Data Vision, which included approximately 190,000 episodes of intensive care unit admissions in Japanese acute care hospitals between April 2008 and September 2021. We used a propensity score-matched analysis to compare outcomes between the IVIG and control groups. Primary outcomes were 28-day mortality, while secondary outcomes included in-hospital mortality, the Barthel Index at discharge, length of hospital stay and laboratory data (albumin, C-reactive protein (CRP), and lymphocyte count) on days 14 and 28.ResultsOf the 17,626 patients enrolled, 15,159 (786 in the IVIG group and 14,373 in the control group) were included in the analysis. Propensity score matching generated 758 matched pairs. Before matching, 28-day mortality and in-hospital mortality were lower in the control group; however, in the matched cohort, 28-day mortality was significantly lower in the IVIG group than in the control group (90/758 [11.9%] vs 124/758 [16.4%]; risk difference [95% confidence intervals (CI)], -4.5% [-8.0% to -1.0%]; P = 0.015). In-hospital mortality in the matched cohort was also significantly more favorable in the IVIG group (137/758 [18.1%] vs 177/758 [23.4%]; risk difference [95%CI], -5.3% [-9.3% to -1.2%]; P = 0.013). Favorable outcomes in terms of albumin on days14 and 28 and CRP levels on day 28 were observed in the IVIG group.ConclusionsThe administration of IVIG was associated with a reduction in sepsis mortality and favorable outcomes in laboratory parameters and the functional status. These results will contribute to the ongoing debate on the efficacy of IVIG for sepsis. The results obtained herein suggest the benefit of IVIG, particularly in mitigating PICS. Further research, including prospective studies, is warranted to confirm these results and examine long-term outcomes.